Grammatical Cohesion in the Short Story "Tanya's Reunion" by Valarie Flournoy (NOBEL: Journal of Literature and Language Teaching, 2017)
This study investigates the types of grammatical cohesion and the frequency of grammatical cohesion in the short story "Tanya's Reunion" By Valarie Flournoy. The study investigation is based on Hasan and Halliday theory of Grammatical Cohesion. This study employs a descriptive qualitative method.The data of this study were taken from the short story entitled "Tanya's Reunion" in the forms of words, phrases, clauses, and sentences. In this study, the researcher is the key instrument who interprets the data. The result of the analysis shows that grammatical cohesion found in the short story "Tanya's Reunion" are reference as personal reference, demonstrative reference, and comparative reference; substitution as nominal substitution and verbal substitution; ellipsis as nominal ellipsis, verbal ellipsis, and clausal ellipsis; and conjunction as additive conjunction, adversative conjunction, causal conjunction, and temporal conjunction, meanwhile, clausal substitution is not found in this short story.